2014
DOI: 10.1016/j.ccr.2014.04.030
|View full text |Cite
|
Sign up to set email alerts
|

RAB7 Controls Melanoma Progression by Exploiting a Lineage-Specific Wiring of the Endolysosomal Pathway

Abstract: Although common cancer hallmarks are well established, lineage-restricted oncogenes remain less understood. Here, we report an inherent dependency of melanoma cells on the small GTPase RAB7, identified within a lysosomal gene cluster that distinguishes this malignancy from over 35 tumor types. Analyses in human cells, clinical specimens, and mouse models demonstrated that RAB7 is an early-induced melanoma driver whose levels can be tuned to favor tumor invasion, ultimately defining metastatic risk. Importantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
130
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 49 publications
7
130
0
1
Order By: Relevance
“…S3). Although this small GTPase is not itself considered a CLEAR network lysosomal gene, Rab7 has been recently shown to play a key role in the regulation of melanoma proliferation by exploiting a lineage-specific endolysosomal pathway wiring (32).…”
Section: Mitf Expression Levels Correlate With Many Lysosomal Genes Inmentioning
confidence: 99%
“…S3). Although this small GTPase is not itself considered a CLEAR network lysosomal gene, Rab7 has been recently shown to play a key role in the regulation of melanoma proliferation by exploiting a lineage-specific endolysosomal pathway wiring (32).…”
Section: Mitf Expression Levels Correlate With Many Lysosomal Genes Inmentioning
confidence: 99%
“…A recent study found that melanomas rely on lysosomal function more than other cancers [66]. Interestingly, the related MiT transcription factors TFEB and TFE3, master lysosomal regulators, can Wnt ligand binding, the destruction complex that phosphorylates and targets ␤-Catenin for proteasomal degradation is recruited to the LRP6 receptor complex, which is endocytosed and subsequently sequestered inside intraluminal vesicles of multivesicular bodies (MVBs).…”
Section: The Mit Family In Cancermentioning
confidence: 99%
“…Among all cancers, melanomas rely on the endolysosomal pathway for growth more strongly than others, and lysosomal genes (plus lysosomal-associated genes such as Rab7) are more highly expressed in melanomas compared to other tumors [66]. Rab7, a small GTPase which has pivotal roles in lysosomal biogenesis and the degradation of lysosomal-associated vesicles [70][71][72], has been recently shown to be an early melanoma driver capable of rewiring the endolysosomal pathway in a lineage-specific fashion [66].…”
Section: Lysosomes and Autophagosomes In Melanomasmentioning
confidence: 99%
See 1 more Smart Citation
“…119,120 Caswell and colleagues established that Rab25 interaction with a5b1 integrin was essential in ovarian epithelial tumor cell invasion into a 3-dimensional fibronectin-enriched ECM and may additionally regulate MMP-dependent regulation. 117,121 Rab coupling protein (RCP), an effector of Rab11 and Rab25, acts as an oncogene as it promotes breast cancer transformation.…”
Section: 93mentioning
confidence: 99%